Dekonstructing the Kardashians : a new media manifesto - Corey, M J, 1990- (Pantheon Books, 2026)
"From the creator of the highly popular Kardashian Kolloquium comes a New Media manifesto for the TikTok age, blending theory and cultural analysis to explain the meteoric rise of the Kardashians and explore what their fame can teach us about the way media functions today. Since 2007, Kim Kardashian and the extended Kardashian family have been mesmerizing--and scandalizing--America. Whether we've liked it or not, we've been inundated with stories of their social lives, scandals, and reality show shenanigans and have witnessed the subsequent ascent of their multibillion-dollar fashion, beauty, and media empire. But the question remains: why are the Kardashians so famous in the first place? And what does this tell us about the New Media that has delivered them to us? In Dekonstructing the Kardashians, MJ Corey, creator of the viral social media presence Kardashian Kolloquium, brings us not only the definitive chronicle of the family that's captivated a nation, but, perhaps more importantly, the story of how media has transformed in the internet age and how it continues to transform us as individuals and as a culture at large. Part media theory, part cultural analysis, Dekonstructing the Kardashians interweaves history from the past 50 years of Western media--from the Old Hollywood studio system to the advent of the 24-hour news cycle to tabloid culture and beyond--with analysis of the cultural influence Kim Kardashian wields over us all and the influences that have shaped her in kind. In so doing, Corey offers proof that the Kardashians are, in fact, the First Family of our image-saturated and deeply divided nation, while also demonstrating how they hold the keys to understanding the schizophrenic, self-referential reality of our current era"-- Provided by publisher.